The Effect of Human Capital on Batik SMEs Innovation: The Mediating Role of Adaptive Creativity - Rini Handayani (Bina Nusantara University, 2020)
The research aimed to examine the role of human capital and adaptive creativity in firm innovation. Using quantitative descriptive methods, the research analyzed 166 batik Small and Medium-Sized Enterprises (SMEs) in Surakarta and Yogyakarta. The sampling technique used was probability sampling methods. The questionnaire as the instrument was sent to the owners of batik SMEs by mail. The data analysis used Structural Equation Modeling (SEM). The results of hypothesis testing show that tacit knowledge and explicit knowledge influence adaptive creativity which affects firm innovation. Individuals who can adapt to tacit and explicit knowledge have good creativity. So, in the end, they can support innovations in the firm. The research findings also strengthen the mediating role of adaptive creativity in the influence of human capital and firm innovation.